Construction and analysis of artificial chromosomes with de novo holocentromeres in Caenorhabditis elegans. Issue 2 (5th August 2020) - Lin, Zhongyang; Yuen, Karen Wing Yee
Abstract: Artificial chromosomes (ACs), generated in yeast (YACs) and human cells (HACs), have facilitated our understanding of the trans -acting proteins, cis -acting elements, such as the centromere, and epigenetic environments that are necessary to maintain chromosome stability. The centromere is the unique chromosomal region that assembles the kinetochore and connects to microtubules to orchestrate chromosome movement during cell division. While monocentromeres are the most commonly characterized centromere organization found in studied organisms, diffused holocentromeres along the chromosome length are observed in some plants, insects and nematodes. Based on the well-established DNA microinjection method in holocentric Caenorhabditis elegans, concatemerization of foreign DNA can efficiently generate megabase-sized extrachromosomal arrays (Exs), or worm ACs (WACs), for analyzing the mechanisms of WAC formation, de novo centromere formation, and segregation through mitosis and meiosis. This review summarizes the structural, size and stability characteristics of WACs. Incorporating LacO repeats in WACs and expressing LacI::GFP allows real-time tracking of newly formed WACs in vivo, whereas expressing LacI::GFP-chromatin modifier fusions can specifically adjust the chromatin environment of WACs. The WACs mature from passive transmission to autonomous segregation by establishing a holocentromere efficiently in a few cell cycles. Importantly, WAC formation does not require any C. elegans genomic DNA sequence. Thus, DNA substrates injected can be changed to evaluate the effects of DNA sequence and structure in WAC segregation. By injecting a complex mixture of DNA, a less repetitive WAC can be generated and propagated in successive generations for DNA sequencing and analysis of the established holocentromere on the WAC.